Current and Emerging Trends in Diabetes Care and Education: 2021 National Practice and Workforce Survey. Issue 5 (October 2022) - Kavookjian, Jan; Bzowyckyj, Andrew S.; DiNardo, Monica M.; Kocurek, Barbara; Kolb, Leslie E.; Noe, Dawn; Ryan, Donna; Saunders, Magon May; See, Michael; Uelmen, Sacha
Purpose: The purpose of the National Practice Survey is to understand current trends related to the diabetes care and education specialist's integration into the full care team beyond formal diabetes self-management education and support services. Methods: The 2021 National Practice Survey (NPS2021) contained 61 questions for all respondents with an additional 56 questions pertaining to specific diabetes care and education segments. An anonymous survey was administered online to respondents who are diabetes care and education specialists or a part of the diabetes care team. Email lists were obtained from the Association of Diabetes Care & Education Specialists (ADCES) and the Certification Board for Diabetes Care and Education (CBDCE). Approximately 39, 258 emails were sent, and 3357 were undeliverable, with 3797 surveys completed between February 9 to April 6, 2021, resulting in an 11% response rate. The response rate may have been affected by the COVID-19 public health emergency. Results: Diabetes care and education specialists represent an interprofessional specialty of nurses, dietitians, physicians, pharmacists, health educators, and others. Many respondents reported holding either certification as a Certified Diabetes Care and Education Specialist (CDCES) or being Board Certified in Advanced Diabetes Management (BC-ADM). In addition, there appears to be a slight increase in those trained as a Lifestyle Coach to provide the National Diabetes Prevention Program (CDC Recognized National DPP) compared to NPS2017. Most respondents reported being Caucasian/White (84%), followed by Hispanic or Latinx (7%) and African American/Black and Asian/Asian American (at 4% each), like in previous surveys. Respondents reported diverse care delivery models, including traditional and nontraditional services, and expanded models of care such as population health/risk stratification models, the Chronic Care Model, Accountable Care Organizations, managed care, and others. Conclusion: The NPS2021 describes DCES workforce opportunities and challenges. Identifying and addressing those that impact the specialty's sustainability, diversity, and growth will guide strategies for the future workforce and their practice settings. Opportunities identified include embracing diabetes community care coordinators for person-centered delivery of care and education services and supporting frontline health care team members to increase competence and expertise in the prevention of type 2 diabetes, diabetes care, and education/support for related chronic diseases. In addition, as health care evolves, it creates opportunities for the DCESs to demonstrate a broader, key role as part of the diabetes care team.